Seasonality of metazoan ectoparasites in marine European flounder Platichthys flesus (Teleostei: Pleuronectidae) - Cavaleiro, FI (2009)
Seasonal occurrence of metazoan ectoparasites is described for the first time in marine European flounder. Platichthys flesus (L.). The parasitofauna, ill this study monitored during I Was found to be similar to that previously recorded for flounder. Moreover, specimens of Caligus sp. Muller, 1785 bind Lepeophtheirus performs (Copepoda: Caligidae), Acanthochondria cornuta (Copepoda: Chondracanthidae), Holobomolochus confusus (Copepoda: Bomolochidae) Mid Nerocila orbignyi (Isopoda: Cymothoidae), and also, a praniza larva (Isopoda: Gnathiidae), were isolated. From these, L.pecotoralis and A. cornuta were the dominant parasites in all samples of flounder, while Caligus sp. H. confusus. N. orbignyi Mid the gnathiid praniza seemed to infect the flounder only occasionally. As far as the seasonality of infections is concerned, it differed considerably from that described for estuarine environments. Indeed, both prevalence and abundance of . pectoralis mid A. cornuta reached significant peaks in the summer, whereas the literature identifies the autumn as the season of maximum infection on estuarine flounder. Thus, the former period seems more favourable for the occurence of epizooties of L. pectoralis and A. cornuta in flounder culturing systems running on seawater and operated in the studied or similar environments.